The Effect of Florfenicol Given by Nebulization in the Treatment of Naturally Infected Calves With Bovine Respiratory Disease Complex: Randomized Clinical Study - Umit Ozcan; Mehmet Tutuncu (Veterinary Medicine and Science)
ABSTRACT Background Bovine respiratory disease (BRD) is still one of the major problems for herd management due to the negative effects on herd health, costs due to treatment, reduced weight gain and calf loss. The aim of this study is to evaluate the effectiveness of aerosolized florfenicol in calves with naturally infected BRD. Methods Forty‐five calves were included in the study and divided into three groups. Group 1 received florfenicol subcutaneous route. While Group 2 received florfenicol administered solely through nebulization, Group 3 received florfenicol via nebulization in addition to flunixin meglumine administered intramuscularly (IM). BRD pathogens were determined from bronchoalveolar lavage (BAL) samples. The treatment period was monitored with a clinical respiratory score, haematology, thorax ultrasonography and serum haptoglobin levels. Results Mycoplasma bovis was the main primary bacterial pathogen isolated from BAL fluid, Escherichia coli was the main secondary bacterial pathogen and bovine respiratory syncytial virus (BRSV) was found to be the primary viral BRD pathogen. The treatment period was shortened to the 2nd day in the groups with nebulization. Calves with clinical respiratory scores of 12 and above died in all groups. There was no significant difference in lung ultrasonographic scoring and haematology results before and after treatment within the groups. There was a significant decrease in the high haptoglobin values before and after the 3rd day of treatment. The study's main limitation was that there was no negative control group in this study due to ethical reasons. Conclusion It was concluded that florfenicol administered by inhalation in BRD patients is more effective, reduces the recovery time and will be a promising treatment strategy.